ROLE OF EDUCATIONAL INSTITUTIONS IN THE ISLAMISATION AND SOCIAL REFORMATION OF DAGHESTAN - Javid Ahmad Bhat; Dr. G. N. Khaki (Fakultas Agama Islam Universitas Wiralodra, 2022)
Islam placed a high value on education, and, as the faith spread among diverse peoples, education became an important channel through which to create a universal and cohesive social order. Consequently, the potential and competence of the individuals are utilized in a desired and productive manner without a slightest deviation from the defined goal. Daghestan inherited two diverse educational approaches known as School and Madrasa educational systems. The aim and objective of both the approaches were to educate and groom the Muslims of the region in religious and modern scientific education and to preserve the rich values and traditions of Muslim civilization from the aggression of colonial powers. Both approaches undoubtedly followed their initial philosophies with zeal and zest. This paper aims to present an inclusive and analytical account of the historicity of educational institutions and traditions in Daghestan. This Study demonstrated various public education centers like Mosque, Maktab and Madrasa have been the main sources of Educational Institutions in northern Caucasus particularly Daghestan.